Ergonomical analysis of partially digitized sound-recording studio - Laugalys, Feliksas; Bagdonas, Albinas (Psichologija, 2003)
This paper provides the comparative ergonomical analysis of traditional and digital sound record studio. There are selected four transitional steps in moving from traditional magnetic tape recoding to digital book: classical (traditional) talking book at the audio studio; installation of digital code in the technology of talking books; audio studio without announcer and studio of full speech synthesis for talking book in this article. A short description of performance of sound studio operator is presented there also. On the basis of Moscow town N enterprises ergonomic analysis of partially digitized sound - recording studio are formulated some ergonomic psychological recommendations for future improvement.